PERAN ORANG TUA DALAM KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK SEKOLAH DASAR - Rahmawati, Rahmawati; Naima, Naima; Nurfaizah, Andi (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2025)
This study aims to identify the role of parents in improving the early reading skills of first-grade students at SD Negeri 1 Tinggede, Marawola Subdistrict, Sigi Regency. The main research questions examined are: (1) What forms of parental involvement are present? and (2) How does such involvement influence children’s reading abilities? This research adopts a descriptive qualitative approach using a case study method, with data collected through interviews, observations, and documentation. The research subjects consist of one first-grade teacher, five parents, and twenty-two students. The data obtained were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that parents play the roles of educators, motivators, and facilitators by accompanying their children in reading, providing reading materials, and creating a conducive learning environment. Among the twenty-two students, seven were categorized as fluent readers, six as moderate, and nine as non-fluent readers. This study highlights the family’s role as a key factor in the development of early literacy skills among children at the primary education level.